Weighted gene co-expression network analysis − based selection of hub genes related to phenolic and volatile compounds and seed coat color in sorghum - Ye-Jin Lee; Woon Ji Kim; Seung Hyeon Lee; Jae Hoon Kim; Soon-Jae Kwon; Joon-Woo Ahn; Sang Hoon Kim; Jin-Baek Kim; Jae Il Lyu; Chang-Hyu Bae; Jaihyunk Ryu (BMC Plant Biology)
Abstract Background Sorghum grains are rich in phenolic compounds, which are noted for their anticancer, antioxidant, and anti-inflammatory properties, as well as volatile compounds (VOCs) that contribute to aroma and fermentation processes. There is a known close relationship between sorghum coat color and phenolic compound content (PCC), particularly flavonoids which are pigments that confer red and purple colors in flowers and seeds. Results Our results showed that black seeds had the highest total tannin content (TTC) and ketone content, which were measured at 457.7 mg CE g-1 and 96 g 100 g-1, respectively, which were 4.87 and 1.35 − fold higher than those of white seeds. L* showed a negative correlation between TTC (r = -0.770, P < 0.01) and ketone (r = -0.814, P < 0.01), while TFC and a* showed a strong positive correlation (r = 0.829, P < 0.001). RNA sequencing analysis identified 1,422 up-regulated and 1,586 down-regulated differentially expressed genes. Weighted gene co-expression analysis highlighted two color-related gene modules: the magenta 2 module associated with TTC, TPC, VOCs and L* value, and the blue module associated with TFC, and a* values. Hub genes identified within these modules included ABCB28 in the magenta 2 module, and PTCD1 and ANK in the blue module. Conclusions We confirmed the relationship between PCC, VOCs, and seed coat color, with darker seed coat colors showing higher tannin, ketone contents and redder colors indicating higher flavonoid content. Network analysis helped pinpoint key genes involved in these traits. This study will provide essential data for improving the food and industrial use of sorghum.